Modified Buck Boost DC-DC Converter with Hyeteresis Band on Ocean Wave Emulator - Purnata, Hendi; Hera Susanti; Sugeng Dwi Riyanto; Agus Santoso (Politeknik Piksi Ganesha Indonesia, 2023)
Indonesia has the potential of sea wave energy with the second largest coastline having a density of up to 20 kW / m2. Currently, the use of sea wave technology is still at the prototype stage, with several weaknesses such as erratic sea waves, tides and ocean currents so that they can affect the power generated in ocean wave energy. The results of ocean wave energy in mechanical arrays cannot be utilized because of erratic waves. The higher the wave, the greater the power generated and vice versa. If this problem is not resolved, it can cause unstable power output and cause damage to electronic equipment. The solution to this problem is to modify the DC-DC buck boost converter circuit using the Hyeteresis band method, which limits voltage surges below or above to produce the desired voltage in order to maintain constant power and as energy for storage in the storage system. The result of this study is that the performance of DC generators in producing voltage is greatly influenced by speed. At low speeds, the voltage produced by the generator is still too low to charge the battery or in other words cannot be in a perfect charging position, while at maximum speed it produces voltage with Achieve a level sufficient for battery charging. Therefore, control and adjustment of generator speed is key in maximizing battery charging efficiency using a buck-boost converter.